EFL Teachers’ Perceptions of the Implementation of Individualized Learning Model: a Case at an English Language Center in Can Tho City : - Ngô, Ngọc Hải (Trường Đại học Cần Thơ, 2018)
The present research is conducted to obtain two research aims. The first aim is to find out the teachers’ perception of the implementation of the individualized learning model. The second aim is to investigate the benefits and difficulties teachers face when they implement the individualized learning model in their classrooms.